Isolation of Streptococcus Thoraltensis in A Case of Necrotizing Fasciitis: Life Sciences-Microbiology - Venkatachalam, Priya; Saikumar, Chitralekha; Raveendran, Praveena (International Journal of Life Science and Pharma Research, 2022)
Our aim of this case report is to add significant epidemiological knowledge regarding the role of Streptococcus thoraltensis in causing human infections, emphasizing the importance of not neglecting the viridans group of streptococci in nonneutropenic patients and also patients with normal cardiac valves. Objectives of our study are to present the clinical features and laboratory findings of a patient diagnosed with Necrotizing fasciitis of perineum in whom S.thoraltesis a viridans streptococcus species was isolated in blood culture . Necrotizing fasciitis is an uncommon bacterial infection of fascial tissue which can progress to cause necrosis followed by sepsis. In microbiological aspects Necrotizing fasciitis is classified as type I and II. Type I is due to polymicrobial infection.Type II is commonly due to group A beta hemolytic Streptococci and Staphylococcus aureus .To the best of our knowledge Streptococcus thoraltensis bacteremia with necrotizing fasciitis has never been reported till now. Only a few cases of S.thoraltensis is reported in literature so far. Here we present a case of a 65-year-old male patient admitted with sepsis and shock. He had a fever, chills for two weeks, and difficulty walking for five days. On examination, there was a scrotal swelling and a swelling of 8x4 cm over the left gluteal region near the anal canal with erythema and tenderness. The computed tomographic scan of the abdomen and pelvis was suggestive of Necrotizing Fasciitis with multiple abscess formation involving perianal region,ischiorectal fossa,root of penis, and scrotum, left anterior abdominal wall with left retroperitoneal and intraperitoneal extension. Laboratory investigations revealed marked neutrophilia and elevated urea and creatinine levels.The patient expired on the same day in spite of prompt supportive treatment. The 2 blood samples drawn from different sites were culture positive for S. thoraltensis . As blood culture results play a very important role in identifying the pathogen in Necrotizing fasciitis S.thoraltensis isolation from two blood cultures throws light on the emerging pathogenic nature of viridans group of streptococci.It emphasizes the importance of treating the viridans group of streptococci and not neglecting it in non-neutropenic patients and patients with normal cardiac valves.